1993
DOI: 10.2307/3431700
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity and Human Chromosomal Effect of Stevioside, a Sweetener from Stevia rebaudiana Bertoni

Abstract: Leaves of Stevia rebaudiana Bertoni have been popularly used as a sweetener in foods and beverages for diabetics and obese people due to their potent sweetener stevioside. In this report, stevioside and steviol were tested for mutagenicity in Salmonella typhimurium strains TA98 and TA100 and for chromosomal effects on cultured human lymphocytes. Stevioside was not mutagenic at concentrations up to 25 mg/plate, but showed direct mutagenicity to only TA98 at 50 mg/plate. However, steviol did not exhibit mutageni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Recently Suttajit et al 7) showed that stevioside, at a high dosage (50 mg/plate), possesses a weak mutagenic activity S9 fraction. Since this observed mutagenic effect could be caused by the impurities present in stevioside.…”
Section: Steviosidementioning
confidence: 99%
See 1 more Smart Citation
“…Recently Suttajit et al 7) showed that stevioside, at a high dosage (50 mg/plate), possesses a weak mutagenic activity S9 fraction. Since this observed mutagenic effect could be caused by the impurities present in stevioside.…”
Section: Steviosidementioning
confidence: 99%
“…4) However, it is known that stevioside is converted to its aglycone, steviol, by intestinal bacteria when orally administered to rats. 5) Pezzuto et al 6) demonstrated that steviol causes a dose-dependent positive response in the forward mutation assay using S. typthimurium TM677 in the presence of a metabolic activation system (Aroclor-induced rat liver S9 fraction).Recently Suttajit et al 7) showed that stevioside, at a high dosage (50 mg/plate), possesses a weak mutagenic activity S9 fraction. Since this observed mutagenic effect could be caused by the impurities present in stevioside.…”
mentioning
confidence: 99%
“…Stevioside of 99% purity showed positive results in Salmonella typhimurium (S. typhimurium) strain TA98 at 50 mg/plate (Suttajit et al 1993). The results of data analysis showed a 4-fold increase in revertants without S9 extract and a 2-fold increase with bacterial strain S9.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The same mutagenic results are shown by both treated and untreated samples which reveal that at 50 mg/plate, stevioside (without β-glucosidase or S9), stevioside metabolite(s) (stevioside + S9), steviol (stevioside + β-glucosidase), and steviol metabolite (s) (stevioside + β-glucosidase + S9) are all mutagenic in TA98. Suttajit et al (1993) also stated that human lymphocytes incubated with 1, 5, and 10 mg/ml stevioside for 24 h did not cause any chromosomal aberrations.…”
Section: Genotoxicitymentioning
confidence: 99%
“…Stevioside does not have teratogenic (Yodyinguard and Bunyawong, 1991), mutagenic (Suttajit et al, 1993) or carcinogenic (Xili et al, 1992) effects.…”
Section: Introductionmentioning
confidence: 99%